Comparison Between Different Endodontic Irrigating Protocols In Smear Layer Removal From Radicular Dentin - Ramona Vlad; Monika Kovacs; Dragos Sita; Mihai Pop (European Scientific Journal, ESJ, 2016)
The aim of our study was to measure the cleaning efficiency of irrigating solutions used during endodontic treatment regarding smear layer removal from the root canal dentin walls. Ethylenediaminotetraacetic acid (EDTA) 17%, citric acid (CA) 10% and sodium hypochlorite (NaOCl) 2,5 % solutions were tested as final irrigating solutions. The study was conducted on extracted teeth, divided in four groups according to the irrigation protocol used. The specimens were analyzed by scanning electron microscopy and the amount of smear layer present at apical, middle and coronal level was recorded, based on a scoring system. Data were statistically analyzed using Kruskal-Wallis and Friedman test and the level of significance was set at p<0.05. In the coronal and middle segments of dental roots we noticed no statistically significant difference between EDTA and CA in smear layer removing capacity. Final irrigation with 17% EDTA proved to be more efficient than 10% CA and 2,5% NaOCl in smear layer removal at apical level of the root canal, with p<0.05 (p=0.042), which is an important area for disinfection in endodontic treatment.